Rewriting of Jin Ping Mei in English : eroticism or exoticism - Tan, Sin Ger (2017)
Jin Ping Mei, the greatest masterwork of Ming novels, continues to be mired in genre classification disputes even today. The banning of the novel in China since the early Qing Dynasty is attributable to its classification as an erotic novel. To most literati and academics, it is not an erotica. Acclamation by Lu Xun that it is the most famous of the novels of manners bears such testimony. Internationally and in China, academic conferences on JPM are held regularly, the most recent of which was the 12th International Academic Conference on JPM held at Jinan University in October last year. In the West, Jing Ping Mei is held in high regard by academics such as Clement Egerton and David Tod Roy. Their rewritings, half a century apart of each other, happened to straddle the sexual revolution in the 1960s, which divided the ideology, poetics and patronage collective into two distinct eras. Roy’s initial attraction to JPM was its reputation of being pornographic but his studies led him to believe it is both a masterwork of Chinese literature and world literature. His skopos is to convey the real China to Americans through his rewriting of JPM, a novel that chronicles the quotidian lives, history and culture of the Chinese people. Roy’s complete rewriting without omitting any of the ST has become an encyclopaedia for researchers around the world today. On the other hand, Egerton’s skopos is anthropological in nature, which led him to omit irrelevant Chinese elements in his rewriting. Constrained by the ideology and poetics imposed on the patronage in his time, he allowed his rewriting to be subjected to literary censorship in the form of manipulation by Latinisation. Statistics has shown that the number of expurgated words is a mere 1.3%, or a miniscule fraction of one percent if we were to only count the objectionable words. As established sinologists, Egerton and Roy would be aware of this proportion. Therefore, based on their rewritings, should JPM be regarded as an erotic novel, or is it in fact an exotic novel? This thesis sets out to explore the theoretical foundation in the rewriting of JPM, the skopos of each of the rewriters as well as the ideology, poetics and patronage that might have constrained rewriters such as Egerton and Roy, whose skopoi and rewritings have elucidated the exoticism of the novel in many ways. Skopos and rewriting are mutually complementary. Products are purpose-driven. Without skopos, there would not be a purpose-driven rewriting. The holistic study of skopos and rewriting would lend authority, credibility and practicality to the existence of rewritings, as well as the applicability and relevance of these rewritings in the target society and culture. The mutual complementariness of skopos and rewriting applies similarly to all literary translations (or rewritings) and the study of these twin factors serves to systemise literature review, rationalise its reception and acceptance, and lay the foundation for other rewriters wishing to embark on a literary translation. Keywords: Jin Ping Mei, Rewriting, Skopos, Ideology, Poetics, Patronage